Catalogue of Coptic and Arabic manuscripts in Dayr al-Suryān - Davis, Stephen J.; Davis, Stephen J.; Suryāni, Bigoul al-; Swanson, Mark N. (Corpus scriptorum Christianorum Orientalium. Subsidia, 2022)
"A catalogue of the Coptic and Arabic collections at Dayr al-Suryan in Wadi al-Natrun, Egypt, to be published in multiple volumes, covering the following genre categories: Biblical Texts, along with Coptic Grammars and Lexica; Commentaries and Canons; Theology; Ascetic Discourses; Saints' Lives and Sermons; and Liturgical Texts. In addition to introducing readers to the history and contents of the monastic library, this series collects data on approximately 1000 manuscripts, recording information on manuscript number and genre, works and contents, date, language, script, and material, scribes, patrons, and restorers, colophons and endowments, pages and numbering systems, dimensions, area of writing, and lines per page, cover and condition, and other details related to scribal practice and readers' insertions. The result will serve as a foundation for further research on Coptic and Christian Arabic literature and on the monastery and its important library." --Provided by publisher